Strategi Pengembangan UMKM Fotocopy Mitra Abadi kawasan Universitas Dharma Andalas - Kirana, E; Aulia, L; Faradika (CV. ITTC INDONESIA, 2025)
Mitra Abadi Photocopy UMKM located in the Dharma Andalas University Campus plays an important role in meeting the needs of photocopying and printing services for students, lecturers, and the surrounding community. Along with the development of digital technology, Mitra Abadi faces the challenge of increasing the visibility and accessibility of its business. One of the strategic efforts made is the development of a website as a means of promotion and online information services. This website is expected to expand market reach, make it easier for customers to obtain service information, and increase operational efficiency through online ordering features. This digitalization project is also a place for students to apply their knowledge and skills in developing technology-based businesses. With the digital transformation, Mitra Abadi is expected to be able to increase competitiveness and provide a positive contribution to the business ecosystem in the Dharma Andalas University campus environment.